Antecedentes da violência doméstica contra as mulheres no Brasil: Origens da família patriarcal - Monteiro (UnB), Anita Cunha (Instituto de Ciências Sociais da Universidade de Brasília, 2013)
Understanding domestic violence in Brazil as a social and sociological problem that affects all of society besides women, this article captures the origins of the traditional family, specifically violence against women. It uses hence the origin of the family in Engels, the influence of family roles in Durkheim’s suicide, the patriarchal family in Gilberto Freyre and the contemporary feminist perspectives through a qualitative and exploratory study that rescue historical elements for contribute to understanding the relationship betweentraditional patriarchal family and domestic violence.